Muscle metabolism during constant- and alternating-intensity exercise around critical power - Brickley, G.; Green, S.; Jenkins, D. G.; McEinery, M.; Wishart, C.; Doust, J. D.; Williams, C. A. (International Journal of Sports Medicine, 2007)
Few studies have focused on the metabolic responses to alternating high- and low-intensity exercise and, specifically, compared these responses to those seen during constant-load exercise performed at the same average power output. This study compared muscle metabolic responses between two patterns of exercise during which the intensity was either constant and just below critical power (CP) or that oscillated above and below CP. Six trained males (mean ± SD age 23.6 ± 2.6 y) completed two 30-minute bouts of cycling (alternating and constant) at an average intensity equal to 90 % of CP. The intensity during alternating exercise varied between 158 % CP and 73 % CP. Biopsy samples from the vastus lateralis muscle were taken before (PRE), at the midpoint and end (POST) of exercise and analysed for glycogen, lactate, PCr and pH. Although these metabolic variables in muscle changed significantly during both patterns of exercise, there were no significant differences (p > 0.05) between constant and alternating exercise for glycogen (PRE: 418.8 ± 85 vs. 444.3 ± 70; POST: 220.5 ± 59 vs. 259.5 ± 126 mmol · kg-1 dw), lactate (PRE: 8.5 ± 7.7 vs. 8.5 ± 8.3; POST: 49.9 ± 19.0 vs. 42.6 ± 26.6 mmol · kg-1 dw), phosphocreatine (PRE: 77.9 ± 11.6 vs. 75.7 ± 16.9; POST: 65.8 ± 12.1 vs. 61.2 ± 12.7 mmol · kg-1 dw) or pH (PRE: 6.99 ± 0.12 vs. 6.99 ± 0.08; POST: 6.86 ± 0.13 vs. 6.85 ± 0.06), respectively. There were also no significant differences in blood lactate responses to the two patterns of exercise. These data suggest that, when the average power output is similar, large variations in exercise intensity exert no significant effect on muscle metabolism.